Chlamydomonas reinhardtii, a green microalga capable of growing in very high light - Virtanen, Olli (My University, 2019)
Plants, algae and cyanobacteria convert sunlight to chemical energy in the process of photosynthesis. Photosynthesis is, however, also damaged by light, mainly through photoinhibition of photosystem II (PSII), which is hindering the overall photosynthetic efficiency. Despite the accelerated photoinhibition in high light, a culture of a wild-type Chlamydomonas reinhardtii, for unknown reasons, has a tendency to start growing when exposed to high light for a prolonged period of time. This study aimed to find out whether the survival of a wild-type culture is caused by selection of already high-light tolerant, individual cells in the original population or by new mutations occurring in high light and how do these high-light-tolerating (HL) cultures differ from the cells grown in moderate light. Cultures of a wild-type C. reinhardtii were inoculated from two types of pre-cultures: ones originating from isolated subpopulations (IS) of the original culture and ones originating from individual cells (SC). Cultures were grown under very high light (PPFD 3000 μmol m-2 s-1) and the IS cultures grew faster and more frequently than the SC cultures, indicating a selection of HL cells in the culture. The resulting phenotype in high light was always the same. Light-saturated oxygen evolution revealed that artificial electron acceptors act as inhibitors of electron transfer in HL cells. HL cultures were also shown to have a larger gap between the redox potentials of QA/QA- and QB/QB- pairs than the control cells. However, HL cultures showed no signs of increased resistance to the damaging reaction of photoinhibition of PSII and the high-light tolerance was at least partly a result of more rapid repair cycle of PSII. The results obtained suggest that there is a common acclimation mechanism that activates within days when exposed to high light. Epigenetic regulation is a promising possibility because the genetic/epigenetic variation seems to contribute to the population’s ability to tolerate the high light and should be examined in the future.
Keywords: Chlamydomonas reinhardtii, high light, photosynthesis, photoinhibition of photosystem II, oxygen evolution, acclimation